PERILAKU SOSIAL ANAK USIA DINI DI LINGKUNGAN LOKALISASI GUYANGAN 2016 - TRI A., FAJAR LUQMAN (JPUD - Jurnal Pendidikan Usia Dini, 2017)
This research aimed to describe the social behavior of children aged 5-6 years in the Localization Guyangan Bagor Nganjuk District of East Java. The study was conducted to early childhood schooling in kindergarten Pertiwi Guyangan village. There are three main subfokus studied were the first form of social behavior, the process of internalization, and three factors supporting and inhibiting the formation of social behavior. The study used a qualitative approach to the type of case study method. Analysis of the data used that model of Miles and Huberman with data collection techniques using observation, interviews, and documentation. Subjects The study focused on children aged 5-6 years amounted to two people. The results showed a positive form of social behavior that develops between the two subjects, namely research cooperation, generosity, caring and adaptable to new people. There was also a negative social behavior is the behavior of the authorities, the dependency will love the attention of others and antagonism of the sexes. The process of internalizing social behavior of which is formed through gift giving, the punishment and the process of imitation. Parenting applied by parents is the subject of research using authoritarian and permissive parenting style is accompanied by violence in applying the rules.